2014
DOI: 10.2217/fmb.14.85
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Bioavailability and Safety of Twice-Daily Topical Ozenoxacin 1% Cream in Adults and Children with Impetigo

Abstract: In this Phase I open-label study, the systemic absorption, clinical response, safety and tolerability of multiple-dose ozenoxacin 1% cream were evaluated in children (≥ 2 months of age) and adults with impetigo. A single (evening) dose of ozenoxacin 1% cream on day 1 was followed by twice-daily application for 4 days (every 12 h), and then a final single (morning) dose on day 6. A total of 46 patients were enrolled in the study. The majority of ozenoxacin plasma samples were below the limit of quantification (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…Another clinical study using a topical 1% ozenoxacin cream has demonstrated a good therapeutic effect in both adult and pediatric patients with impetigo [14]. It is assumed that these therapeutic effects of topical ozenoxacin on superficial skin infections are based on the potent antimicrobial activity of the drug against MSSA, MRSA and S. pyogenes as shown in this study.…”
mentioning
confidence: 58%
“…Another clinical study using a topical 1% ozenoxacin cream has demonstrated a good therapeutic effect in both adult and pediatric patients with impetigo [14]. It is assumed that these therapeutic effects of topical ozenoxacin on superficial skin infections are based on the potent antimicrobial activity of the drug against MSSA, MRSA and S. pyogenes as shown in this study.…”
mentioning
confidence: 58%
“…The efficacy and safety of ozenoxacin in the paediatric population with non-bullous impetigo were examined by pooling data for patients aged 6 months to < 18 years of age who had participated in phase I [20] or phase III [10,11] clinical trials. In the combined population, clinical and microbiological success rates with ozenoxacin were significantly superior to those with vehicle, confirming the results of the pivotal phase III trials.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled efficacy and safety population consisted of 529 patients aged ≥6 months to < 18 years with non-bullous impetigo who were enrolled in phase I [20] or phase III [10,11] clinical trials of ozenoxacin. Most patients were recruited in South Africa (n = 313), the USA (n = 79), or Germany (n = 60).…”
Section: Demographics and Baseline Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…68 In a phase I open label study involving 46 patients (adult and pediatric), systemic bioavailability was undetectable in all but four samples, indicating minimal systemic exposure to topical ozenoxacin. 70 Another phase I trial studied the skin tissue exposure of topical ozenoxacin 2% dosed either once or twice daily. Results indicated that the drug does not penetrate well into the dermis, steady state conditions are reached at day three, and skin concentrations correlate linearly with total amount of drug administered.…”
Section: Phase III Agentsmentioning
confidence: 99%